Ayo Bercerita: Meningkatkan Minat Baca Anak Lewat Dongeng - Hariyana, Baiq; Haifaturrahmah, Haifaturrahmah; Nizaar, Muhammad (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to identify and analyze various research findings on the effectiveness of storytelling activities in improving reading interest among elementary school students. The research employs a Systematic Literature Review (SLR) approach by examining scholarly articles published between 2015 and 2025 sourced from Google Scholar, DOAJ, and Scopus. A total of 75 studies were reviewed, and 24 met the inclusion criteria based on topic relevance, research design, and discussion focus. The findings reveal that storytelling significantly enhances children’s reading interest through affective (emotional and motivational), cognitive (story comprehension and vocabulary), and social (interaction and empathy) dimensions. Storytelling not only serves as entertainment but also as a contextual literacy medium that fosters joy and engagement in reading from an early age. Furthermore, the emergence of digital storytelling platforms has expanded children’s access to engaging reading materials, thereby increasing their motivation to read. The study concludes that both traditional and digital storytelling practices play a vital role in cultivating a sustainable reading culture among Indonesian children.